"A pit to put women in": professionalism, work intensification, sexualisation and work–life balance in the legal profession in England and Wales. Issue 1 (2nd January 2016) - Sommerlad, Hilary
Abstract: Today, the rhetorical commitment to diversity and inclusion is almost universally espoused across the legal profession in England and Wales, and issues such as the position of women lawyers and alternative ways of working are recurring themes in the trade press. Yet statistical evidence clearly reveals a profession segmented by gender: its powerful and well remunerated positions remain overwhelmingly occupied by white men, and its working practices continue to require a professional identity unencumbered by responsibility for social reproduction. This paper draws on qualitative research to flesh out this picture and to reflect on some of the mechanisms which produce women's sub-professional status – which, it is argued, include the discourse of professionalism. Some themes identified by respondents – such as hyper-masculine work cultures in which women figure as backrooms technicians – are longstanding. Other themes concern either new developments or a deepening of trends already under way, which appear to be having a particularly adverse impact on women's working conditions. These trends include the intensification of work; the heightened significance of client care, leading to the development of 'boundary spanning roles' that generate even greater demands in terms of time and emotional labour, and the accentuation of misogyny and harassment consequent on the eclipse of traditional gentlemanly professionalism by a sexualised corporate culture. Under these conditions the possibility of the profession developing working conditions which offer work–life balance appears remote.